A Cross-sectional Study of Linguistic Creativity of Hindi Language Learners in Relation to their Academic Achievement - Sharma, Anjali; Rawat, Neha; Pinku, (JOURNAL OF INDIAN EDUCATION, 2021)
The present study is a cross-sectional study of language creativity in Hindi language learners to explore its relationship with academic achievement, conducted through a descriptive survey research method. The sample for the study was taken from the population of secondary level students of Class IX. A sample size of 800 respondents has been chosen based on stratified random sampling technique by random selection of participants from three strata, namely: (i) Background (Urban and Rural), (ii) Type of school (Government and Private), and (iii) Gender (male and female). A standardised verbal language creativity test designed by S. Malhotra and Sucheta Kumari has been used to test language creativity and the scores of class VIII final examination have been taken as the measure of academic achievement of learners of different levels. One-way ANOVA and t-test in the statistical tools were employed to test null hypotheses. The conclusions of the study establish that the language creativity in Hindi language learners in writing skills is affected by their academic achievements levels. Therefore, by augmenting the academic achievement of language learners, their language creativity can be improved along with the Hindi writing skills and expressions.